Inventory of medium- to large-sized wild mammals from District Nagar, Gilgit-Baltistan, Pakistan through camera-trap surveys - Shahab Din; Joong Yeol Park; Mihyeon Kim; Sungwon Hong (Biodiversity Data Journal)
The study area is located within the Central Karakoram National Park, nestled in the towering Karakoram mountain range. Situated at high altitude in the District of Nagar, Gilgit-Baltistan, Pakistan, this region is characterised by its rugged terrain, glaciers and snow-covered peaks. The area encompasses diverse habitats, including alpine meadows, subalpine forests and glaciated zones, which provide potential habitat for medium- to large-sized mammals. Despite its ecological significance, wildlife in this area remains understudied. Therefore, the current study aimed to document the wild mammal species of the high-altitude Hoper and Hisper Valleys.Camera-trapping surveys were conducted from April to November 2024 to record wild medium- to large-sized mammals in the study area. Thirty trail cameras were deployed across the study area, which resulted in 85 occurrence records for seven mammal species, including three carnivores, two lagomorphs, one rodent and one ruminant. All species were native, non-endemic to the region. According to the IUCN Conservation Status, Panthera uncia (Snow Leopard), Mustela altaica (Mountain Weasel) and Capra sibirica (Himalayan Ibex) belong to the endangered categories. Out of the seven mammals recorded in this study, five are newly documented, while the Snow Leopard and Himalayan Ibex have been previously reported from the area. The data collected from this survey provide valuable occurrence information on the mammal species present in the study area, which can serve as a baseline for monitoring and conservation efforts in the future.